I DO NOT KNOW: HOW CHRISTIAN EDUCATORS CAN HELP AGNOSTIC STUDENTS - Ezra Iskandar; Felix Tanzil (Universitas Kristen Petra, 2024)
A growing number of Indonesian young people, both on campuses and social media, are identifying as agnostics. However, many do so without fully understanding what agnosticism means, often seeing it as an anti-mainstream alternative to atheism. This trend presents a challenge for educators, particularly in Christian schools and universities, who must engage with these students effectively. In the Indonesian context, this issue is further complicated by Pancasila, which upholds belief in God as national ideology. This essay uses recent literature to introduce the basic tenets of agnosticism, identify types of agnosticism, and offer educators practical strategies – from theology, philosophy, and psychology – to foster deeper understanding of this issue in schools.